PENGALAMAN GURU MENGENAI DINAMIKA BUDAYA SEKOLAH DALAM IMPLEMENTASI PLATFORM PEMBELAJARAN DIGITAL (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe teachers' experiences in implementing digital learning platforms such as Canva, Wordwall, and Wayground in elementary schools. A qualitative phenomenological approach was used to understand teachers' subjective experiences during the process of using digital platforms. The research informants consisted of two classroom teachers and one principal selected through purposive sampling. Data collection was conducted through in-depth interviews and documentation studies of digital teaching materials. Data analysis followed the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results of the study revealed two main experience patterns: gradual digital adaptation and support that facilitated implementation. The implementation of digital platforms was influenced by teacher self-efficacy, perceived benefits of technology, and the availability of technical and environmental support. This study emphasizes the importance of teacher readiness and technology access in supporting the effective use of digital platforms in elementary schools.